Dispersion of the soybean root rot by Cycloneda sanguinea (Coleoptera: Coccinellidae) - Salgado-Neto, Geraldo; Braz Vaz, Marcos Andre; Carus Guedes, Jerson Vanderlei; Briao Muniz, Marlove Fatima; Blume, Elena; Wilcken, Carlos Frederico [UNESP]; Castro e Castro, Barbara Monteiro de; Plata-Rueda, Angelica; Zanuncio, Jose Cola (Nature Publishing Group, 2018)
The dispersion of pathogenic microorganisms consists of the transport of pathogens from their source to inoculate a new host. Agricultural and economic importance of the Soybean root rot justifies studying this disease, especially the role of insects as dispersers. The aim of this study was to evaluate the role of the ladybird beetle, Cycloneda sanguinea Linnaeus (Coleoptera: Coccinellidae) in the dispersion of pathogens that cause Soybean root rot. Three pathogen species, Macrophomina phaseolina (Tassi) (Sphaeropsidales: Botryosphaeriaceae), Fusarium incarnatum-equiseti species complex (FIESC), and F. commune (Skovgaard) O'Donnell & Nirenberg were isolated from the midgut of ladybird beetles and cultured. Macrophomina phaseolina was identified by morphology while for the other two species, DNA was sequenced. The DNA extracted was amplified in the Internal Transcriber Spacer (ITS) region, sequenced and compared to voucher sequences deposited in the GenBank. Sequences of nucleotide ITS1-5.8 S were identified in the regions of rDNA-ITS4 ribosomal DNA. This is the first report of Macrophomina phaseolina (Tassi) (Sphaeropsidales: Botryosphaeriaceae), Fusarium incarnatum-equiseti species complex (FIESC), and F. commune (Skovgaard) O'Donnell & Nirenberg, being dispersed by C. sanguinea in Brazilian soybean fields.